Pengaruh Kesehatan Bank terhadap Harga Saham - Ahmad Junaidi; Bayu Rangges Setiawan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of risk profile, good corporate governance and capital on stock returns in banking companies listed on the Indonesia Stock Exchange in 2017-2019. This type of research is quantitative research. The research sample is 27 banking companies. The data analysis method used is multiple linear regression. The data analysis technique used multiple linear regression processed using SPSS 25. The results showed that risk profile and good corporate governance has no effect on stock returns except earnings and capital positive significant effect on stock return.